Crystallization of an engineered RUN domain of Rab6-interacting protein 1/DENND5. - FERNANDES, HUMBERTO; FRANKLIN, EDWARD; KHAN, AMIR RAFIQ (International Union of Crystallography, 2011)
Effectors of the Rab small GTPases are large multi-domain proteins which have proved difficult to express in soluble form in Escherichia coli. Generally, effectors are recruited to a distinct subcellular compartment by active (GTP-bound) Rabs, which are linked to membranes by one or two prenylated Cys residues at their C-termini. Following recruitment via their Rab-binding domain (RBD), effectors carry out various aspects of vesicle formation, transport, tethering and fusion through their other domains. Previously, successful purification of the RUN-PLAT tandem domains (residues 683-1061) of the 1263-residue Rab6-interacting protein 1 (R6IP1) required co-expression with Rab6, as attempts to solubly express the effector alone were unsuccessful. R6IP1 is also known as DENN domain-containing protein 5 (DENND5) and is expressed as two isoforms, R6IP1A/B (DENND5A/B), which differ by 24 amino acids at the N-terminus. Here, a deletion in R6IP1 was engineered to enable soluble expression and to improve the quality of the crystals grown in complex with Rab6. A large 23-residue loop linking two -helices in the RUN1 domain was removed and replaced with a short linker. This loop resides on the opposite face to the Rab6-binding site and is not conserved in the RUN-domain family. In contrast to wild-type R6IP1-Rab6 crystals, which took several weeks to grow to full size, the engineered R6IP1 (RPdel)-Rab6 crystals could be grown in a matter of days.
PUBLISHED
Keywords: Immunology; Infection; Escherichia coli